Multi‐generational long‐distance migration of insects: studying the painted lady butterfly in the Western Palaearctic. Issue 4 (16th October 2012) - Stefanescu, Constantí; Páramo, Ferran; Åkesson, Susanne; Alarcón, Marta; Ávila, Anna; Brereton, Tom; Carnicer, Jofre; Cassar, Louis F.; Fox, Richard; Heliölä, Janne; Hill, Jane K.; Hirneisen, Norbert; et al.
<x xml:space="preserve">Abstract</x> Long‐range, seasonal migration is a widespread phenomenon among insects, allowing them to track and exploit abundant but ephemeral resources over vast geographical areas. However, the basic patterns of how species shift across multiple locations and seasons are unknown in most cases, even though migrant species comprise an important component of the temperate‐zone biota. The painted lady butterfly Vanessa cardui is such an example; a cosmopolitan continuously‐brooded species which migrates each year between Africa and Europe, sometimes in enormous numbers. The migration of 2009 was one of the most impressive recorded, and thousands of observations were collected through citizen science programmes and systematic entomological surveys, such as high altitude insect‐monitoring radar and ground‐based butterfly monitoring schemes. Here we use V. cardui as a model species to better understand insect migration in the Western Palaearctic, and we capitalise on the complementary data sources available for this iconic butterfly. The migratory cycle in this species involves six generations, encompassing a latitudinal shift of thousands of kilometres (up to 60 degrees of latitude). The cycle comprises an annual poleward advance of the populations in spring followed by an equatorward return movement in autumn, with returning individuals potentially flying thousands of kilometres. We show that many long‐distance migrants take advantage of favourable winds, moving downwind at high elevation (from some tens of metres from the ground to altitudes over 1000 m), pointing at strong similarities in the flight strategies used by V. cardui and other migrant Lepidoptera. Our results reveal the highly successful strategy that has evolved in these insects, and provide a useful framework for a better understanding of long‐distance seasonal migration in the temperate regions worldwide.